Myeloid cell iron uptake pathways and paramagnetic rim formation in multiple sclerosis - Hofmann, Annika; Krajnc, Nik; Dal-Bianco, Assunta; Riedl, Christian J.; Zrzavy, Tobias; Lerma Martin, Celia; Kasprian, Gregor; Weber, Claudia E.; Pezzini, Francesco; Leutmezer, Fritz; Rommer, Paulus; Bsteh, Gabriel; et al. (Acta neuropathologica, 2023)
In multiple sclerosis (MS), sustained inflammatory activity can be visualized by iron-sensitive magnetic resonance imaging (MRI) at the edges of chronic lesions. These paramagnetic rim lesions (PRLs) are associated with clinical worsening, although the cell type-specific and molecular pathways of iron uptake and metabolism are not well known. We studied two postmortem cohorts: an exploratory formalin-fixed paraffin-embedded (FFPE) tissue cohort of 18 controls and 24 MS cases and a confirmatory snap-frozen cohort of 6 controls and 14 MS cases. Besides myelin and non-heme iron imaging, the haptoglobin-hemoglobin scavenger receptor CD163, the iron-metabolizing markers HMOX1 and HAMP as well as immune-related markers P2RY12, CD68, C1QA and IL10 were visualized in myeloid cell (MC) subtypes at RNA and protein levels across different MS lesion areas. In addition, we studied PRLs in vivo in a cohort of 98 people with MS (pwMS) via iron-sensitive 3 T MRI and haptoglobin genotyping by PCR. CSF samples were available from 38 pwMS for soluble CD163 (sCD163) protein level measurements by ELISA. In postmortem tissues, we observed that iron uptake was linked to rim-associated C1QA-expressing MC subtypes, characterized by upregulation of CD163, HMOX1, HAMP and, conversely, downregulation of P2RY12. We found that pwMS with $$\ge
Online veröffentlicht: 16. September 2023
Gesehen am 06.08.2024